Hambatan dalam Pelaksanaan Layanan Bimbingan dan Konseling di Sekolah - Hengka Nove, Albertus (Jurnal Bimbingan dan Konseling Pandohop, 2026)
The primary task of school counselors is to support students in achieving their developmental tasks in accordance with the Student Independence Competency Standards (SKKPD) at each stage of development. Therefore, school counselors require adequate support, collaboration with various stakeholders, and sufficient facilities and infrastructure to perform their roles effectively. However, in practice, school counselors often encounter various challenges. This study aims to identify the obstacles faced by school counselors in delivering guidance and counseling services in educational institutions. A qualitative approach was employed through semi-structured interviews with one counselor, identified by the initials “NR,” at a public junior high school in Palangka Raya. Data analysis was conducted through data reduction, presentation, and verification. The findings reveal several challenges faced by the counselor, including limited understanding of stakeholders regarding the counselor’s duties and functions; an excessive student-to-counselor ratio exceeding 150 students, with some students being uncooperative; additional workload that hinders service focus; counseling rooms that do not meet standardized requirements; curriculum changes requiring service format adjustments; and limited reference books to support guidance and counseling services.